Probabilistic-based characterisation of the mechanical properties of CFRP laminates - Gomes, S.; Dias-da-Costa, D.; Neves, L.A.C.; Hadigheh, S.A.; Fernandes, P.; Júlio, E. (Elsevier, 2018)
Fibre reinforced polymer (FRP) composites have been increasingly used worldwide in the strengthening of civil engineering structures. As FRP becomes more common in structural strengthening, the development of probability-based limit state design codes will require accurate models for the prediction of the mechanical properties of the FRPs. Existing models, however, are based on small sample sizes and ignore the importance of the tail region for analyses and design. Addressing these limitations, this paper presents a probabilistic-based characterisation of the mechanical properties of carbon FRP (CFRP) laminates using a large batch of tension tests. The analysed specimens were pre-cured laminates of carbon fibres embedded in epoxy matrices, which is the most commonly used laminate for the strengthening concrete beams and slabs. Based on the existing data, probabilistic models and correlations were established for the Young's modulus, ultimate strain and tensile strength. Analyses demonstrate the suitability of the Weibull distribution for the estimation of CFRP properties. Results also show that the statistical characterisation of the mechanical properties should be performed with a focus on the tail region. The proposed distributions constitute a set of validated probabilistic models that can be used for performing reliability analyses of structures strengthened with CFRP laminates.